Language arts : content and teaching strategies - Tompkins, Gail E.; Bright, Robin M.; Pollard, Michael J.; Winsor, Pamela J. T. (Canada : Prentice hall, 1998)
A text for beginning teachers that presents the content of the language arts curriculum and the effective strategies for teaching it to students in kindergarten through eighth grade. It reflects a constructivist approach to teaching and learning.
Includes bibliographical references and indexes.
Keywords: Language arts (Elementary).